A Microstructural Study of Destabilised 30wt%Cr-2.3wt%C High Chromium Cast Iron - Wiengmoon A. (2014)
An as-cast 30wt%Cr-2.3wt%C cast iron was destabilised in the temperature range of 900-1 100°C for times of 2-8 h, followed by air cooling to room temperature. The resultant microstructures were examined using light microscopy (LM), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Volume fractions of secondary carbide within the martensite matrix and of M23C6 in eutectic carbides were determined. Vickers macrohardness and Vickers microhardness of the dendritic regions were also measured. It was found that morphologies of secondary carbide were cube, plate-like shape or discrete-rod. A duplex core-shell structure was found in the eutectic carbides after destabilisation. It consists of M7C 3 as a core surrounding by M23C6, while the secondary carbide in these alloys was identified as M23C6. Higher destabilisation temperatures resulted in coarser secondary carbides with comparable volume fraction, but less in counts per area. The volume fraction of M23C6 within the duplex structure was also increased when increasing destabilisation temperature and time. The results from hardness measurements revealed that the overall macrohardness of the iron was increased with increasing the destabilisation temperature up to about 770 HV (30 kgf/15 s) at 1 025°C, whereas the microhardness of the dendritic regions reached the maximum value of 800 HV (100 gf/15 s) at about 1 025°C.